2021
DOI: 10.1002/pc.26386
|View full text |Cite
|
Sign up to set email alerts
|

Diatomite‐filled epoxy resin composites: Curing behavior, dielectric, and thermal properties

Abstract: In this study, a kind of novel curing agent composed of acrylic acid and 4,4 0 -(hexafluoroisopropylidene)bis(p-phenyleneoxy)dianiline was mixed, with different contents of diatomite (CP) particles, into the epoxy resin (E51) to obtain bio-composites that can be rapidly molded and cured at room temperature. Fourier Transform Infrared Spectroscopy and Differential Scanning Calorimetry were used to study the curing behavior of epoxy resin and biocomposites. The influence of CP particle dosages on the mechanical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…A small amount of oxygen was carried into the pores of diatomite, thus promoting the oxidative decomposition of the composite. The addition of PEI‐KH560‐DE reduced the maximum thermal weight loss rate and slowed down the thermal decomposition of the epoxy resin 39 . Moreover, the addition of raw‐DE and PEI‐KH560‐DE substantially increased the char yield of the epoxy resin system at 600°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A small amount of oxygen was carried into the pores of diatomite, thus promoting the oxidative decomposition of the composite. The addition of PEI‐KH560‐DE reduced the maximum thermal weight loss rate and slowed down the thermal decomposition of the epoxy resin 39 . Moreover, the addition of raw‐DE and PEI‐KH560‐DE substantially increased the char yield of the epoxy resin system at 600°C.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of PEI-KH560-DE reduced the maximum thermal weight loss rate and slowed down the thermal decomposition of the epoxy resin. 39 Moreover, the addition of raw-DE and PEI-KH560-DE substantially increased the char yield of the epoxy resin system at 600 C. In comparison with the 14.10 wt% char yield of pure epoxy resin at 600 C, the char yield of PEI-KH560-DE/EP composite reached 25.30 wt%, corresponding to a 79.43% increase in char yield. PEI-KH560-DE enhanced the heat resistance and thermal stability of the epoxy resin.…”
Section: Thermal Performance Testing and Curing Kinetics Of Epoxy Res...mentioning
confidence: 92%
“…The evaluation encompassed measurements of the storage modulus in MPa, providing insights into material stiffness, as well as the Tan (δ), which quantifies the correlation between stored elastic energy and energy dissipated per vibration cycle. [35][36][37] The thermomechanical attributes of these composites are contingent on diverse parameters, encompassing the nature and quantity of the reinforcing phase. Consequently, alterations in these conditions lead to distinct values for the modulus and glass transition temperature (Tg).…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…The results showed that the incorporation of diatomite could dramatically improve the mechanical and thermal stability of the epoxy composites. Yuan et al 34 mixed a novel curing agent consisting of acrylic acid and 4,4 0 -(hexafluoroisopropylidene) bis(p-phenyleneoxy)dianiline with different contents of diatomite (CP) particles and added them to epoxy resin (E51), prepared biobased composites that could be rapidly molded and cured at room temperature. The effects of the amount of CP particles on the mechanical (tensile, flexural, and impact) and thermal properties of the composites were discussed.…”
Section: Introductionmentioning
confidence: 99%